Evaluation of Long-Term Stability in Single-Piece Implant Systems: An Original Research - Arshdeep S. Kohli; Manjiri Salkar; Jeevan Matada Basavarajaiah; Vishakha Ugale; Harsh Chansoria; Sajni Rai; Mohammed Mustafa (Wolters Kluwer Medknow Publications, 2024)
Background: Because of its integrated design and possible benefits over conventional two-piece systems, single-piece implant systems have grown in favor in the field of dental implantology. There is, however, still a dearth of information about their long-term stability and clinical results. The purpose of this study was to assess the clinical results, such as implant survival rates, peri-implant tissue health, and marginal bone levels, to determine the long-term stability of single-piece implant systems. Methods: About 127 individuals who got single-piece implants at the tertiary care center were the subject of a retrospective analysis. Standardized procedures were followed for implant implantation, and patients were monitored for at least five years afterward. Through radiographic analysis and clinical tests, clinical indicators such as marginal bone levels, peri-implant tissue health, and implant survival rates were evaluated. Results: With low marginal bone loss and good peri-implant tissue health, the research showed a high implant survival rate of 96.5%. A statistical study revealed significant relationships between marginal bone loss (P < 0.01), peri-implant tissue health (P < 0.05), and implant survival. Conclusion: In this study, single-piece implant devices showed good long-term durability and clinical results. These results confirm its effectiveness as a dependable dental rehabilitation alternative, highlighting the significance of preserving the health of the peri-implant tissue and reducing marginal bone loss to guarantee implant success.